2014
DOI: 10.1155/2014/420616
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gamma Irradiation on Structural and Biological Properties of a PLGA-PEG-Hydroxyapatite Composite

Abstract: Gamma irradiation is able to affect various structural and biological properties of biomaterials In this study, a composite of Hap/PLGA-PEG and their ingredients were submitted to gamma irradiation doses of 25 and 50 KGy. Various properties such as molecular weight (GPC), thermal behavior (DSC), wettability (contact angle), cell viability (MTT assay), and alkaline phosphatase activity were studied for the composites and each of their ingredients. The results showed a decrease in molecular weight of copolymer w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 39 publications
3
32
0
4
Order By: Relevance
“…This research confirmed significant decrease of polymer molecular weight due to the chain scission mechanism. They showed that gamma irradiation caused insignificant decrease of T g and T m and a slight decrease of the contact angle in this copolymer . However, there is no information about the effect of nanoparticle incorporation on the PLGA structure and its mechanical properties after sterilization by gamma irradiation.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…This research confirmed significant decrease of polymer molecular weight due to the chain scission mechanism. They showed that gamma irradiation caused insignificant decrease of T g and T m and a slight decrease of the contact angle in this copolymer . However, there is no information about the effect of nanoparticle incorporation on the PLGA structure and its mechanical properties after sterilization by gamma irradiation.…”
Section: Introductionmentioning
confidence: 98%
“…Radiation may also be used for chemical modification of the polymer samples' surface to improve cell adhesion . Unfortunately, in some polymers, such as PLGA, sterilization by gamma radiation significantly changes the properties by reducing the molecular weight . The mechanism of degradation does not depend on the type of radiation used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A esterilização por radiação gama é um método que tem-se mostrado bastante eficiente para tratar materiais médicos ou farmacêuticos [263][264][265]268,270]. Devido ao aumento da utilização de dispositivos médicos descartáveis nos últimos anos, houve um aumento considerável na utilização desse tipo de procedimento.…”
Section: Esterilização De Materiais Para Aplicações Biomédicasunclassified
“…Alguns trabalhos reportam a influência da radiação nas propriedades do PLGA usando altas doses, porém, estudos mostrando a influência de baixas doses usadas para esterilização (~ 25 kGy) são escassos [264,270,272,274]. Embora a dose de 25 kGy seja considerada padrão para esterilização de dispositivos médicos, doses menores podem ser utilizadas, se a validação do processo for possível [265,271].…”
Section: Esterilização De Materiais Para Aplicações Biomédicasunclassified